PENGGUNAAN BERBAGAI AGEN PEMADAM DALAM PENANGANAN KEBAKARAN KENDARAAN LISTRIK - Supri, Supri; Sapurta, Surya Tri; Nugraha , Wildan (Langit Biru: Jurnal Ilmiah Aviasi, 2024)
Background: Electric Vehicles (EV) have become a popular choice as an environmentally friendly transportation alternative. The Indonesian government supports the use of electric vehicles through various policies. However, the increasing number of electric vehicles brings new challenges, particularly related to safety, namely electric vehicle fires. The development and implementation of handling strategies are needed considering electric vehicle fires are unique and different from conventional vehicle fires. The use of extinguishing agents is believed to have a significant impact in addressing electric vehicle fire challenges. Method: Scoping Review following the PRISMA-ScR guidelines with a PEO framework. Searches through Science Direct and Google Scholar from 2014 to 2024, article filtering using Mendeley and Covidence. Results: A total of 230 articles were obtained, after which article filtering was conducted, selecting 9 articles that were relevant and met the criteria. This review identifies three main themes: types of extinguishing agents, methods of use, and trial results. Groups of solid, liquid, gas, foam, and chemical extinguishing agents can be used alone or in combination, showing the effectiveness of extinguishing agents in lowering temperatures to address fire hazards associated with electric vehicles. Conclusion: The use of various extinguishing agents has proven effective in handling electric vehicle fires.